Takotsubo Syndrome After Cardiopulmonary Resuscitation During Emergency Cesarean Delivery. Issue 3 (March 2017) - Kraft, Katrina; Graf, Matthias; Karch, Martin; Felberbaum, Ricardo
Abstract : BACKGROUND: Takotsubo syndrome is a rare, stress-related, and reversible form of acute heart failure primarily affecting postmenopausal women. It is characterized by left ventricular dysfunction with a classic apical and midventricular wall motion abnormality (apical ballooning). CASE: A 28-year-old woman, gravida 2 para 1, at 30 4/7 weeks of gestation was admitted with fetal bradycardia, a fully dilated cervix, and breech presentation. During emergency cesarean delivery, the patient had intraoperative cardiac arrest. Resuscitation was successful. Twelve hours postoperatively, after demonstrating symptoms of acute heart failure, she was diagnosed with Takotsubo syndrome. CONCLUSION: Peripartum Takotsubo syndrome must be differentiated from peripartum cardiomyopathy. Cesarean delivery and sympathomimetic medications can increase the risk of occurrence. Early recognition and interdisciplinary management are essential in the prevention of serious and potentially fatal complications. Abstract : Cesarean delivery is considered an obstetric risk factor for Takotsubo syndrome, and early recognition and interdisciplinary management are essential to morbidity and mortality reduction.